STRATEGI PENINGKATAN HAFALAN AL-QUR’AN SANTRI MELALUI METODE TADZAKIRUS SIYAHAH : STRATEGI PENINGKATAN HAFALAN AL-QUR’AN SANTRI MELALUI METODE TADZAKIRUS SIYAHAH - Abbas, Moh. Jailani; Sugiono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the strategies for enhancing Qur’an memorization among students through the Tadzakirus Siyahah method. Using a qualitative case study design, the research was conducted at Madrasatul Qur’an, Pondok Pesantren Nurul Qur’an, Kraksaan Probolinggo, from January to May 2025. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman framework, which includes data collection, reduction, display, and conclusion drawing. The findings reveal that the Tadzakirus Siyahah method is an integrated system covering three stages: pre-memorization, memorization, and post-memorization. The pre-memorization stage involves group recitation, takriran–murāja‘ah, the one day one juz program, and motivational reinforcement. The memorization stage emphasizes sima’an subuh, individual and collective murāja‘ah, and contextual rihlah ilmiah–siyahah. The post-memorization stage includes report checking, peer tasmi‘, achievement record books, and participation in Emqi Ber-MTQ. These strategies serve not only as evaluative instruments but also as mechanisms for retention enhancement and the cultivation of Qur’anic character among students.This study contributes to the discourse on Qur’an memorization pedagogy by highlighting the holistic nature of Tadzakirus Siyahah as both a methodological framework and a character-building approach.